Accounting the reinforcing efficiency and percolating role of interphase regions in tensile modulus of polymer/CNT nanocomposites. (February 2017) - Zare, Yasser; Rhee, Kyong Yop
Graphical abstract: Highlights: The reinforcing efficiency and percolating effect of interphase in PCNT are studied. The interphases around the dispersed and networked nanoparticles are accounted. The interphase percolation is considered by thickness of interphase and CNT dimensions. The validity of the developed model is evaluated by the experimental results. Abstract: In this work, a micromechanics model is developed for tensile modulus that incorporates the reinforcing efficiency and percolating effects of the interphase in polymer/CNT nanocomposites (PCNT). More specifically, Takayanagi model is developed to account interphases around dispersed and networked nanoparticles. The interphase percolation is considered in the model by the thickness of the interphase, as well as the radius and length of CNT, which can affect the percolation threshold of nanoparticles and concentration of the filler network. The validity of the developed model is evaluated by some experimental results. Similarly, the effects of all parameters attributed to dispersed and networked nanoparticles as well as interphases on the modulus of PCNT are studied. Based on the developed model, the high values of some parameters such as interphase thickness, interphase modulus between the polymer matrix and networked nanoparticles, network modulus, fraction of nanoparticles in the network, and network density improve the modulus of PCNT, whereas the radius and percolation threshold of nanoparticles have an adverse effect.